2013
DOI: 10.3389/fnint.2013.00062
|View full text |Cite
|
Sign up to set email alerts
|

Hyperleptinemia is associated with parameters of low-grade systemic inflammation and metabolic dysfunction in obese human beings

Abstract: Leptin is an adipose tissue-derived hormone that has been involved in hypothalamic and systemic inflammation, altered food-intake patterns, and metabolic dysfunction in obese mice. However, it remains unclear whether leptin has a relationship with parameters of systemic inflammation and metabolic dysfunction in humans. We thus evaluated in a cross-sectional study the circulating levels of leptin in 40 non-obese and 41 obese Mexican individuals, examining their relationship with tumor necrosis factor alpha (TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 38 publications
8
37
0
5
Order By: Relevance
“…In contrast, many studies have investigated these relationships in obese and normal individuals. 22 In the present study the increase in BMI from the first to forth quartile of leptin levels was statistically significant (p<0.000), indicating the role of leptin as a biomarker of obesity. With the exception of HDL-cholesterol, the study variables showed a statistically significant increase from the first to the forth quartile of leptin levels.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast, many studies have investigated these relationships in obese and normal individuals. 22 In the present study the increase in BMI from the first to forth quartile of leptin levels was statistically significant (p<0.000), indicating the role of leptin as a biomarker of obesity. With the exception of HDL-cholesterol, the study variables showed a statistically significant increase from the first to the forth quartile of leptin levels.…”
Section: Discussionmentioning
confidence: 60%
“…In some of them leptin levels were positively related with IR [17][18], but in others no statistical significances were reached [19]. In the present study, we did not reach any difference in leptin levels between groups.…”
Section: Prace Oryginalnesupporting
confidence: 33%
“…The correlation of leptin levels with IR has been studied in many reports [17][18][19]. In some of them leptin levels were positively related with IR [17][18], but in others no statistical significances were reached [19].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Por otro lado, se ha descrito que la leptina incrementa los niveles de AU 41 , teniendo relevancia ya que en los sujetos con obesidad mórbida se ha descrito la presencia de hiperleptinemia, aunque no se ha precisado el mecanismo por el cual esto acontece 42 . El AU mostró una tendencia no significativa a ser mayor en los sujetos que además tenían SMet, y a su vez estos pacientes con obesidad mórbida mostraron los valores más altos de PCR y TNF-α, y más bajos de IL-10.…”
Section: Figura 2 Coeficientes De Correlación De Pearson Al Evaluar unclassified